CDMX Resilient Code: Water Commons in Mexico City - Bello Gómez, Lorena (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
Using Mexico City (CDMX) as a paradigmatic example of seriously unbalanced water regimes, our project Resilient Code helps strengthen and communicate CDMX’s government efforts toward risk reduction and water resilience in marginal communities. Our project does so by bridging otherwise separate agents in the government towards a common goal: equitable resilience. Resilient Code provides design solutions that link the social infrastructure of PILARES (a network of 300 vocational schools distributed throughout the city) to CDMX’s environmental and risk reduction initiatives, including their Risk Atlas. This strategic program of design-based solutions began with “water resilience” as a Pilot to repurpose public space throughout underserviced barrios as a network of “water-commons”. Resilient Code helps partners in CDMX implement projects to reduce environmental risks and complement socio-economic programs, fostering growth of the “water-commons”. Resilient Code is socialized through a participatory game-based workshop, and through an online Atlas of Risk Reduction.
Keywords: Water Imaginary; Equitable Resilience; Resilient Code; Soft-Bottom Up Infrastructure; Water Commons; Hydro-Social Risk Reduction